2016
DOI: 10.1111/jdv.13689
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life and disease severity in patients with atopic dermatitis

Abstract: AD impacts negatively on the QoL, proportional to the severity of the disease. Furthermore, female sex and facial eczema are associated with low QoL. Positive FLG null mutation status is not associated with QoL or disease severity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
74
3
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(92 citation statements)
references
References 37 publications
9
74
3
6
Order By: Relevance
“…Mozaffari et al found that patients perceived dressing, undressing, and bath time as being most problematic, while the dimension “family activities” was least affected. Holm et al also found that dressing was particularly problematic. Using the EQ‐5D as a measure of QoL, daily activity, and pain/discomfort parameters were reported to be most affected in patients .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Mozaffari et al found that patients perceived dressing, undressing, and bath time as being most problematic, while the dimension “family activities” was least affected. Holm et al also found that dressing was particularly problematic. Using the EQ‐5D as a measure of QoL, daily activity, and pain/discomfort parameters were reported to be most affected in patients .…”
Section: Resultsmentioning
confidence: 99%
“…Mean overall DLQI scores ranged across studies from 4.9 (small effect on patient's QoL) to 20.5 (very large effect on patient's QoL). In studies which looked at differences across the dimensions of QoL, the areas that were most affected as measured using the DLQI were symptoms and feelings surrounding AD; patients felt embarrassed or self‐conscious because of their AD, and symptoms such as itchy, sore, painful, and stinging skin had a detrimental impact on their QoL . Personal relationships were the least affected dimension of QoL .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Facial eczema could indicate a more negative influence of AD, as shown in the child cohort by the impact on self-rated health compared to non-CAM users. It may constitute a significant disease burden for the patient, and previous studies have documented that facial skin disease affects quality of life significantly more in a negative direction than other locations [13, 23-25], which could be speculated to drive CAM use. Facial eczema is challenging and not always satisfyingly treated by conventional treatments, therefore patients with facial eczema may be willing to try any possible solution.…”
Section: Discussionmentioning
confidence: 99%
“…Empiriniai tyrimai ir sisteminės tyrimų apžvalgos atskleidžia emocinę asmens būklę ir jo patiriamus sunkumus esant susijusius ne vien su AD, tačiau ir su kitų dermatologinių ligų (psoriazės, dilgėlinės, seborėjos, aknės) raiška bei jų eiga. Odos ligomis sergančių asmenų grupėje nustatomi aukštesni nerimo, depresijos, socialinės disfunkcijos ir žemesni pasitenkinimo gyvenimu ir gyvenimo kokybės įverčiai, šioje grupėje būdingesnė nemiga [36,[40][41][42][43][44]. Taip pat tyrimai pagrindžia socialinės paramos reikšmingumą bei integruoto tarpdisciplininio požiūrio į dermatologinių ligų gydymą svarbą [41].…”
Section: Atopiniu Dermatitu Sergančio Vaiko Emocinio Funkcionavimo Ypunclassified